Structural characterization of copper (II) tetradecanoate with 2,2′-bipyridine and 4,4′-bipyridine to study magnetic properties - Bedowr, Noha Said; Yahya, Rosiyah; Farhan, Nesrain (Elsevier, 2018)
This paper presents synthesis, structural characterization and spintronic applications of copper (II) tetradecanoate derived magnetic complexes. The complexes were prepared by a chemical reaction between [Cu2(CH3(CH2)12COO)4](EtOH)2 and 2,2′-bipyridine-4,4′-bipyridine ligands respectively. The complexes were further reacted between the product of the first reaction and 4,4′-bipyridine-2,2′-bipyridine respectively. The structural characterization techniques included elemental analysis, Fourier transformed infrared spectroscopy (FTIR), Ultra-violet–Visible (UV–Vis) spectroscopy, polarized optical microscopy, magnetic moment and thermogravimetric analysis. The structural and characterization results suggested that the synthesized complexes were binuclear and mononuclear covalent complexes of copper(II) with structural formulas [Cu2(η2-(OOCR)4](4,4′-bpy)2H2O] and [Cu(η1-(OOCR)2(2,2′-bpy) (4,4′-bpy)] respectively.